Exploring Copper’s role in stroke: progress and treatment approaches - Peng, Gang; Huang, Yongpan; Xie, Guangdi; Tang, Jiayu (Frontiers in Pharmacology, 2024)
Copper is an important mineral, and moderate copper is required to maintain physiological processes in nervous system including cerebral ischemia/reperfusion (I/R) injury. Over the past few decades, copper induced cell death, named cuprotosis, has attracted increasing attention. Several lines of evidence have confirmed cuprotosis exerts pivotal role in diverse of pathological processes, such as cancer, neurodegenerative diseases, and I/R injury. Therefore, an in-depth understanding of the interaction mechanism between copper-mediated cell death and I/R injury may reveal the significant alterations about cellular copper-mediated homeostasis in physiological and pathophysiological conditions, as well as therapeutic strategies deciphering copper-induced cell death in cerebral I/R injury.